2006
DOI: 10.1007/s00330-006-0157-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated cardio-thoracic imaging with ECG-Gated 64-slice multidetector-row CT: initial findings in 133 patients

Abstract: The purpose of this study was to investigate the possibility of assessing the underlying respiratory disease as well as cardiac function during ECG-gated CT angiography of the chest with 64-slice multidetector-row CT (MDCT). One hundred thirty-three consecutive patients in sinus rhythm with known or suspected ventricular dysfunction underwent an ECG-gated CT angiographic examination of the chest without beta-blockers using the following parameters: (1) collimation: 32 x 0.6 mm with z-flying focal spot for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 13 publications
(20 reference statements)
1
22
0
Order By: Relevance
“…The mean duration of data acquisition was 18.11±2.67 s (range: [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. In our study group, 127 patients (95%) had coronary arteries that could be partially or totally assessed; coronary artery imaging failed in six patients (5%), due to a poor level of enhancement achieved within coronary arteries in five patients (i.e., attenuation values below 200 HU) and alteration of image quality by interpolation artefacts in one patient with a heart rate of 45 bpm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean duration of data acquisition was 18.11±2.67 s (range: [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. In our study group, 127 patients (95%) had coronary arteries that could be partially or totally assessed; coronary artery imaging failed in six patients (5%), due to a poor level of enhancement achieved within coronary arteries in five patients (i.e., attenuation values below 200 HU) and alteration of image quality by interpolation artefacts in one patient with a heart rate of 45 bpm.…”
Section: Resultsmentioning
confidence: 99%
“…In the studied population, CT was indicated for the management of bronchopulmonary (n=102) or pulmonary vascular (n=31) diseases. Detailed description of the studied population and scanning parameters have been reported in a separate study [12]. In the same group of patients who did not receive β-blockers prior to CT scanning, the objective of the present study was to investigate the assessability of coronary arteries acquired by a routine ECG-gated MDCT examination of the chest.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from coronary imaging, ECG-gated examinations of the chest can also provide cardiac functional information, of great interest in respiratory patients. Investigating 133 patients with a regular sinus rhythm who did not receive betablockers, Salem et al found that both morphological and functional information could be obtained from the same data set in 92% of the population studied with singlesource MDCT [41]. These recent experiences suggest that respiratory patients can now benefit from cardiothoracic imaging, a concept worth considering in the management of patients with chronic obstructive pulmonary disease (COPD) in whom coronary arteries represent a well-known target of systemic inflammation [42][43][44].…”
Section: Discussionmentioning
confidence: 95%
“…without compromising image quality (7,8). Depending on the thoracic dimensions, the scanning time varied between three and four seconds.…”
Section: Resultsmentioning
confidence: 99%